Investment Decisions in Manufacturing Companies in Indonesia - Farhan, Muhammad; Kurniawati, Dian; Iqbal, Muhammad; Maulani, Denia (INOVATOR, 2023)
This study aims to analyze the effect of capital structure, profitability, liquidity, and company size on the value of manufacturing companies in various sectors and asset groups as a fundamental analysis tool in investment decisions. The object of research is a manufacturing compa-ny listed on the Indonesia Stock Exchange for the 2015-2018 period. 117 companies were selected using the purposive sampling method. The research data is secondary data, namely audited financial reports obtained through the official website of the Indonesia Stock Exchange. The data analysis technique uses panel data regression. Simultaneously capital structure, profitability, liquidity, and firm size have a signifi-cant effect on firm value. Partially, capital structure, profitability, li-quidity, and company size show different results with different effects on the firm value both for manufacturing as a whole, as well as by sec-tor and asset group.